Ataxia-telangiectasia: A new remitting form with a peculiar transcriptome signature - Leuzzi, Vincenzo (Neurol Genet, 2018)
OBJECTIVE: Ataxia-telangiectasia (AT) is a rare, severe, and ineluctably progressive multisystemic neurodegenerative disease. Variant AT phenotypes have been described in patients with mild- and late-onset neurologic deterioration and atypical features (dystonia and myoclonus). We report on the clinical characteristics and transcriptome profile of patients with a typical AT presentation and genotype who experienced an unexpected favorable course. METHODS: A 24-year-old woman developed, by the age of 3 years, all the classic symptoms of AT associated with increased alpha-fetoprotein levels, a compound AT-mutated (ATM) genotype with an inframe deletion c.2250G>A (p.Glu709_Lys750del42) and a missense mutation c.8122G>A (p.Asp2708Gln), and no residual ATM protein expression. By the age of 12 years, ataxia slowly disappeared, and a very mild choreic disorder was the only neurologic feature in adulthood. Brain MRI was normal. The blood transcriptome profile was assessed and compared with that of healthy controls and patients with the classic AT phenotype. RESULTS: The atypical clinical course of the patient was associated with a transitional transcriptome profile: while 90% of transcripts were expressed as in patients with the classic AT presentation, 10% of transcripts were expressed as in healthy controls. CONCLUSIONS: The unexpected mild clinical outcome and transcriptome profile of this patient with AT suggest the existence of individual resilience to the altered ATM synthesis. Because of their possible prognostic and therapeutic implications, the identification of modifier factors affecting the phenotype would deserve further studies.